Compressive strength of high-strength concrete masonry grouted prisms. (30th March 2019) - Fonseca, Fernando S.; Fortes, Ernesto S.; Parsekian, Guilherme A.; Camacho, Jefferson S.
Highlights: Mortar, grout and CMUs of different strengths are used to construct masonry prisms. Influence of grout strength on the masonry compressive strength is evaluated. Grouts without and with a shrinkage-compensating admixture is evaluated. No statistically difference between strengths of grouted prisms at 14 and 28 days. Depending on the combination of the materials used, grouted masonry can be less or more efficient than ungrouted masonry. Abstract: An experimental program was devised to assess the influence of the compressive strength of the grout on the compressive strength of masonry constructed with high-strength concrete masonry units. Three different compressive strengths of mortar, grout, and concrete masonry units were used. Grouts were made without and with a shrinkage-compensating admixture. The various components were combined to construct several hollow and grouted prisms, which were then tested. The results show that very high-strength blocks were not as efficient as medium-strength blocks and that there was a difference between the compressive strengths of ungrouted and grouted masonry; depending on the combination of the materials used, grouted masonry can be less or more efficient than ungrouted masonry. For one combination of materials, the shrinkage-compensating admixture was shown to be effective in reducing the grout shrinkage, and the grouted prisms constructed with that combination of materials were more efficient than their hollow prisms counterpart. Grouted prisms constructed with grouts without the shrinkage-compensating admixture were, on average, less efficient than hollow prisms. The efficiency of grouted masonry depends on many factors including compatibility of deformation between the masonry components, compaction of the grout, shrinkage characteristics of the grout, block geometry, and bond between grout and block. Further research is needed to determine the influence of these factors and obtain a complete understanding of the behavior and capacity of high strength masonry.